Observed Teaching Practices and Motivation as Predictors of Student Engagement in Mathematics - Rose Marie Normandia; Ken Justine Malnegro; Zenny Joy Caman; Arabela Jala; Abel Sadji (Goodwood Publishing, 2026)
Purpose: The primary purpose of this study aimed to investigate whether observed teaching practices and motivation significantly predict student engagement in the Bachelor of Secondary Education Major in Mathematics. Research Methodology: A quantitative descriptive-predictive research design was used, with simple random sampling to select 54 second-year Bachelor of Secondary Education students majoring in Mathematics from Davao del Norte State College. Three validated questionnaires were used to measure these variables. Statistical analyses included the mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. Results: Significant positive relationships were found between teaching practices (r= 0.543) and students’ motivation (r=0.658), and student engagement. Both teaching practices (β=0.40) and students' motivation (β=0.49) were significant predictors of student engagement. The adjusted R-squared value of 0.59 indicates that the model explains 59% of the variation in student engagement. Conclusions: Teaching Practices and student motivation are significant predictors of student engagement among second-year Bachelor of Secondary Education (BSEd) Mathematics students. Limitations: The study was limited to 54 second-year BSEd Mathematics students from a single institution and used self-reported questionnaire data, which may limit generalizability and overlook other factors affecting students’ engagement. Contributions: This study provides empirical evidence of the predictive role of teaching practices and motivation in student engagement and offers implications for instructional improvement, teacher education, and future mathematics education research.